Evaluation of Oral Health Status and Oral Care of Patients with Rheumatoid Arthritis - Małgorzata Radwan-Oczko; Irena Duś-Ilnicka; Pamela Richards; Anna Marie Thomsen; Claus Rasmussen (Hindawi Limited, 2020)
Objective. Rheumatoid arthritis (RA) and periodontal disease (PD) are common chronic, immunoinflammatory, destructive, and progressive diseases; however, the correlations between those two are not yet widely discussed. The purpose of this study was to evaluate the relationship between the selected demographic and clinical parameters of RA patients and oral health status parameters, on the basis of self-assessment. Materials and Methods. Three hundred patients under treatment were included in the study. Questionnaires were completed by 164 out of 300 patients. Results. A total of 100 females and 64 males took part in the study, with a mean age of 65 ± 11.1 years. In younger patients, the disease activity score (DAS28) was higher, and it was associated with pain or discomfort in the oral cavity and with difficulties in toothbrushing. Discomfort or pain in the oral cavity was to a significant extent associated with the poor gingival state, gingival bleeding, and difficulties in biting or chewing. Conclusions. In RA patients, difficulties in biting or chewing, discomfort or pain in oral cavity, feeling of the presence of movable teeth, and gingival bleeding are indications of periodontal infection. Maintaining awareness of oral health and RA is a key issue in the simultaneous management of proper oral care and RA due to the mutual influence of those two factors.